Targeting Syk in Autoimmune Rheumatic Diseases - Deng, Guo-Min; Kyttaris, Vasileios C.; Tsokos, George C. (Frontiers in Immunology, 2016)
.Spleen tyrosine kinase (Syk) is a member of the Src family of non-receptor tyrosine kinases which associates directly with surface receptors including B cell receptor and Fcγ receptor and is involved in a variety of signal transduction pathways. Rheumatoid arthritis and systemic lupus erythematosus are autoimmune disease in which autoantibodies, immune complexes and autoreactive T cells account for the expression of tissue inflammation and damage. Syk inhibitors efficiently suppress rheumatoid arthritis in patients albeit in the expression of unwanted side effects including gastrointestinal effects, hypertension and neutropenia. Syk inhibitors also inhibit clinical manifestations in lupus-prone mice. Here we review the evidence which supports the use of Syk inhibitors to treat rheumatic and other autoimmune diseases